Promoting agency and identity building in dialogic learning communities online - Sorensen, Elsebeth Korsgaard; Brooks, Eva Irene (Proceedings of the International Conference on Networked Learning, 2018)
For several decades educational institutions and their educational designers have waited for a significant innovation and pedagogical breakthrough in digitally based teaching and learning (Bates, 2015; Bruce, 2016; Conole, 2013; Tait, 2013; Sorensen & Brooks, 2017). New innovative approaches and pedagogies were expected in design of teaching and learning; approaches which, methodologically, would acknowledge basic human qualities and inter-human co-existential virtues and functionalities. Such approaches, as e.g. dialogue, collaboration, communication, creativity, improvisation, may be viewed to be relevant to any topic addressed, as pertinent values for developing and empowering robust identities. However, as it stands, new and innovative pedagogical paradigms for teaching and learning seem to have stagnated. The authors of this paper make a plea for the use of fundamental human concepts, features and inter-human functionalities - such as e.g. a focus on concepts of relational agency, dialogue and dialogic, identity, which may produce very fruitful teaching and learning processes through restoring, implementing and operationalizing fundamental motivating principles of development processes of the human nature. This paper reports on an explorative study of the learning dialogue in an online module, one module of an online master’s part-time program in Ict and Learning. The philosophy behind the design and organization of the program is inspired from the Project Oriented Project Pedagogy (POPP) approach, introduced at Aalborg University (AAU) at its very birth in 1974. The paper focuses on the use, role, potential and implications for teaching and learning when using a digital dialogic learning pedagogy built on the basic principles of POPP and unfolding in virtual learning environments. Through the analytical lenses of the theoretical concepts such as “identity” and “agency”, the authors set out to explore the extent to which online dialogues and potentially identified signs of developed identity, and agency in learners, may promote inclusion and contribute as very important meta learning values for the cultivation of awareness in citizens in our future global society. The analytical optic is formed from a perspective of some key concepts of theorists, such as the notion of “relational agency” by Edwards (2006 & 2007), the notion of “dialogic” by Wegerif (2007) and the idea of “co-creation” (Sanders, 2008). The methodological approach is inspired by the principles of Netnography[1] and is a continuation of the authors’ serious of earlier studies on inclusive online learning dialogues and their implications for learning in digital environments (e.g. Sorensen & Brooks, 2017). The findings of this study suggest that for networked learning of including quality, co-creation, identity and relational agency are important elements for learners to obtain and be exposed to. All of these concepts appear very close to the essential aspects of human nature. [1] Netnography uses these conversations as data. It is an interpretive research method that adapts the traditional, in-person participant observation techniques of anthropology to the study of interactions and experiences manifesting through digital communications (Kozinets, R. V, 2010)